The Iceland Deep Drilling Project 4.5 km deep well, IDDP-2, in the seawater-recharged Reykjanes geothermal field in SW Iceland has successfully reached its supercritical target - Friðleifsson, Guðmundur Ó.; Elders, Wilfred A.; Zierenberg, Robert A.; Stefánsson, Ari; Fowler, Andrew P. G.; Weisenberger, Tobias B.; Harðarson, Björn S.; Mesfin, Kiflom G. (Scientific Drilling, 2017)
The Iceland Deep Drilling Project research well RN-15/IDDP-2 at Reykjanes, Iceland, reached its target of supercritical conditions at a depth of 4.5 km in January 2017. After only 6 days of heating, the measured bottom hole temperature was 426 °C, and the fluid pressure was 34 MPa. The southern tip of the Reykjanes peninsula is the landward extension of the Mid-Atlantic Ridge in Iceland. Reykjanes is unique among Icelandic geothermal systems in that it is recharged by seawater, which has a critical point of 406 °C at 29.8 MPa. The geologic setting and fluid characteristics at Reykjanes provide a geochemical analog that allows us to investigate the roots of a mid-ocean ridge submarine black smoker hydrothermal system. Drilling began with deepening an existing 2.5 km deep vertical production well (RN-15) to 3 km depth, followed by inclined drilling directed towards the main upflow zone of the system, for a total slant depth of 4659 m ( ∼ 4.5 km vertical depth). Total circulation losses of drilling fluid were encountered below 2.5 km, which could not be cured using lost circulation blocking materials or multiple cement jobs. Accordingly, drilling continued to the total depth without return of drill cuttings. Thirteen spot coring attempts were made below 3 km depth. Rocks in the cores are basalts and dolerites with alteration ranging from upper greenschist facies to amphibolite facies, suggesting that formation temperatures at depth exceed 450 °C. High-permeability circulation-fluid loss zones (feed points or feed zones) were detected at multiple depth levels below 3 km depth to bottom. The largest circulation losses (most permeable zones) occurred between the bottom of the casing and 3.4 km depth. Permeable zones encountered below 3.4 km accepted less than 5 % of the injected water. Currently, the project is attempting soft stimulation to increase deep permeability. While it is too early to speculate on the energy potential of this well and its economics, the IDDP-2 is a milestone in the development of geothermal resources and the study of hydrothermal systems. It is the first well that successfully encountered supercritical hydrothermal conditions, with potential high-power output, and in which on-going hydrothermal metamorphism at amphibolite facies conditions can be observed. The next step will be to carry out flow testing and fluid sampling to determine the chemical and thermodynamic properties of the formation fluids.